Oportunidades agroindustriales en la Cuenca del Pacífico - Bailey, William C.; Norina, Lidia V. (Universidad ESAN. ESAN Ediciones, 1997)
Compares the possibilities of New Zealand and Peru in export agriculture and agribusiness, in which both countries have great potential. He considers that, to remain competitive internationally, both countries must stop exporting raw materials and replace them with products with higher added value. It analyzes the situation and the expected evolution of four New Zealand export products: meat, milk and derivatives, venison and kiwi, and argues that the central aspect to take advantage of the challenges and opportunities in agribusiness is to never forget the importance of the consumer and the consumption patterns, as the importance given to products sensitive to the environment is growing. As possible strategies, mention is made of taking advantage of the comparative advantages offered by nature, developing products specifically destined for the export market, protecting natural resources while maintaining the international competitiveness of agribusiness.

Compara las posibilidades de Nueva Zelanda y Perú en agricultura exportadora y agronegocios, en los que ambos países tienen gran potencial. Considera que, para seguir siendo competitivos a nivel internacional, ambos países deben dejar de exportar materias primas y sustituirlas por productos de mayor valor añadido. Analiza la situación y la evolución esperada de cuatro productos de exportación de Nueva Zelanda: carne, leche y derivados, venado y kiwi, y sostiene que el aspecto central para aprovechar los desafíos y oportunidades del agronegocio es no olvidar nunca la importancia del consumidor. y los patrones de consumo, ya que crece la importancia otorgada a los productos sensibles al medio ambiente. Como posibles estrategias se menciona aprovechar las ventajas comparativas que ofrece la naturaleza, desarrollar productos destinados específicamente al mercado de exportación, proteger los recursos naturales manteniendo la competitividad internacional de los agronegocios.
Keywords: Agriculture; Agribusiness; Competitive advantages; Agricultura; Agroindustria; International trade; Ventaja competitiva; New Zealand; Comercio internacional; Nueva Zelanda; Peru; Perú; https://purl.org/pe-repo/ocde/ford#5.02.04